La République islamique d’Iran face à l’URSS (1979-1984) : Realpolitik ou répulsion? - Vaner, Semih (Études internationales, 1986)
A few authors, while comparing the foreign policy of the Shah with that of khomeiny, have come to the conclusion either of a "total break" or, conversely, of a "continuity" with regard to the policy of Iran towards the Soviet Union. However, keeping only the Soviet Union in mind, but viewed from various levels in time and space, one can observe a break which derives from ideological incompatibility, then again a continuity which result s from some kind of realization of internal or external pressures. The fear arising from a threatening contiguity, the diplomatic isolation which followed the seizing of power in 1979, the pressure of political forces favourable to the USSR, the Kurdish minority in search of external allies, especially from the north, the ruinous war with Irak, the geopolitical constraints are such that the fundamentalists have not followed through their hostility to the end, in spite of its being fed by a series of historical resentments. The attitude of Iran towards the USSR still remains a real stake in its internal policy. The revolutionary turmoil has brought about a less blurred image of the USSR despite some confusion, an image once varied, then becoming apparently unified. The course of relations between Iran and the USSR depends to a great extent on the internal dynamics of the Iranian revolution, but also on the political evolution in the Middle East and on the new power struggle which could come about in that region.